RV vacations for dummies / Shirley Slater, Harry Basch - Slater, Shirley
Shows you how to get the most out of your RV vacations with tips on choosing the right route and the right season for travel. This guide also helps you select a suitable RV which you can afford. It offers guidance on eating and sleeping comfortably on the road. It also includes tips on what you shouldn't miss - and what you can skip.